(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2021)
Abstract: In the Indian banking sector, Electronic customer relationship management is concerned with maintenance and optimization of long lasting valuable relationships with the consumers. The current study analyzed the relationship between demographic characteristics ‘Electronic customer relationship management services’ and service quality perceived by consumers related to E-CRM practices. Primary data was collected using a survey method. The structured questionnaires were distributed to 600 respondents, where 455 responses came out. After collection of data, ANOVA has been used to analyze the difference between the means of period of availing banking services with service quality dimensions. The major findings revealed that consumer perception was significantly different in service quality dimensions “Assurance” and “empathy” in public sector banks. It can be said that tenure of banking has a significant effect on consumers of both private and public sector banks.